2012
DOI: 10.1075/gest.12.1.02mur
|View full text |Cite
|
Sign up to set email alerts
|

Gestural-vocal coordination

Abstract: Esta es la versión de autor del artículo publicado en: This is an author produced version of a paper published in:Gesture 12.1 (2012): 16-39 DOI: http://dx.doi.org/10.1075/gest.12.1.02mur Copyright: © John Benjamins Publishing CompanyEl acceso a la versión del editor puede requerir la suscripción del recurso Access to the published version may require subscription AbstractThe aim of this study was to examine longitudinally gestural and vocal coordination in multimodal communicative patterns during the period … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
17
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 38 publications
4
17
0
1
Order By: Relevance
“…This finding is consistent with previous research showing the predictive character of pointing with vocalization (Igualada et al, 2015;Murillo & Belinchón, 2012; Gros-Louis, 2014) on later language abilities, and the relevance of declarative function on this pointing predictive role (Colonnesi et al, 2010).…”
supporting
confidence: 93%
See 1 more Smart Citation
“…This finding is consistent with previous research showing the predictive character of pointing with vocalization (Igualada et al, 2015;Murillo & Belinchón, 2012; Gros-Louis, 2014) on later language abilities, and the relevance of declarative function on this pointing predictive role (Colonnesi et al, 2010).…”
supporting
confidence: 93%
“…Murillo and Belinchón (2012) found that the coordinated use of gesture (specifically, pointing), vocalization and social gaze at 1;0 is a strong predictor of lexical development three months later. Wu and GrosLouis (2014) also found that gesture-vocal coordination was related to infants' linguistic skills at 1;3.…”
mentioning
confidence: 95%
“…To our knowledge only two studies have explored the predictive role of early simultaneous gesture-speech combinations on later language development. In Murillo and Belinchón (2012), a sample of eleven parent-infant dyads were recorded interacting in a semistructured play context at three longitudinal moments, namely at 9, 12, and 15 months. The results showed that the use of pointing gestures at 12 months, especially when accompanied by vocalizations and directed gaze on the part of the infant, correlated positively with vocabulary development at 15 months of age.…”
Section: Introductionmentioning
confidence: 99%
“…By using an experimental task which favors a specific declarative intention from the child and which controls for the adult's patterns of responses, we aim at extending results elicited in research by Murillo and Belinchón (2012) and Wu and Gros-Louis (2014) through an experimental task where infants are not interacting with their mothers. This controlled scenario will allow us to more thoroughly analyze the connection between infants' communicative strategies and their language outcomes 6 months later (measures in those studies were obtained just 3 months later, at 15 months of age).…”
Section: Introductionmentioning
confidence: 99%
“…However, these rhythmic movements are not yet communicative (Ejiri & Masataka, 2001). The first communicative gestures, pointing gestures, start being produced in isolation around 8-10 months of age (Bates et al, 1975) and it is not until around 15 months of age that infants combine most of their pointing gestures with speech (Butcher & Goldin-Meadow, 2000;Igualada et al, under review;Murillo & Belinchón, 2012). In these gesture-speech combinations it seems that infants are already able to temporally align gesture and speech in an adult-like way, since (1) gestures start before the vocalizations associated with them, (2) the stroke onset coincides with the onset of the prominent syllable in speech, and (3) the gesture apex is produced before the end of the accented syllable (Esteve-Gibert & Prieto, 2014).…”
mentioning
confidence: 99%